A practical approach to remote longitudinal follow‐up of Parkinson's disease: The FOUND study. Issue 6 (11th February 2014) - Tanner, Caroline M.; Meng, Cheryl C.; Ravina, Bernard; Lang, Anthony; Kurlan, Roger; Marek, Kenneth; Oakes, David; Seibyl, John; Flagg, Emily; Gauger, Lisa; Guest, Dolores D.; Goetz, Christopher G.; et al.
ABSTRACT The objective of this study was to examine a remote method for maintaining long‐term contact with Parkinson's disease (PD) patients participating in clinical studies. Long‐term follow‐up of PD patients is needed to fill critical information gaps on progression, biomarkers, and treatment. Prospective in‐person assessment can be costly and may be impossible for some patients. Remote assessment using mail and telephone contact may be a practical follow‐up method. Patients enrolled in the multi‐center Longitudinal and Biomarker Study in Parkinson's Disease (LABS‐PD) in‐person follow‐up study in 2006 were invited to enroll in Follow‐up of Persons With Neurologic Diseases (FOUND), which is overseen by a single center under a separate, central institutional review board protocol. FOUND uses mailed questionnaires and telephone interviews to assess PD status. FOUND follow‐up continued when LABS‐PD in‐person visits ended in 2011. Retention and agreement between remote and in‐person assessments were determined. In total, 422 of 499 (84.5%) of eligible patients volunteered, AND 96% of participants were retained. Of 60 patients who withdrew consent from LABS‐PD, 51 were retained in FOUND. Of 341 patients who were active in LABS‐PD, 340 were retained in FOUND (99.7%) when the in‐person visits ceased. Exact agreement between remote and in‐person assessments was ≥ 80% for diagnosis, disease features (eg, dyskinesias), and PD medication. Correlation between expert‐rated and self‐reported Unified Parkinson's Disease Rating Scale and Movement Disorder Society Unified Parkinson's Disease Rating Scale, which were examined at times separated by several months, was moderate or substantial for most items. Retention was excellent using remote follow‐up of research participants with PD, providing a safety net when combined with in‐person visits, and also is effective as a stand‐alone assessment method, providing a useful alternative when in‐person evaluation is not feasible. © 2014 International Parkinson and Movement Disorder Society